Enterprise Data Workflow Automation: A Technical Guide to Implementation and Best Practices - Suman Ankampally (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive technical article explores the revolutionary field of business data workflow automation, covering best practices and crucial implementation factors in a range of organizational areas. In addition to offering insights into upcoming trends, the study looks at technological implementation stacks, development frameworks, security protocols, real-world applications, and strategic planning approaches. This article illustrates how businesses can successfully switch from manual to automated workflows while preserving operational integrity and optimizing efficiency through in-depth industry studies and scholarly research analysis. The article presents detailed assessments of Python-based automation ecosystems, enterprise-grade tools, iterative development approaches, and risk management strategies. It further explores the interplay between technical and business process automation, emphasizing the importance of balanced implementation approaches. The article highlights crucial success factors, including proper goal-setting frameworks, comprehensive security measures, and effective change management strategies, while also addressing the emerging trends in AI integration and hyper-automation possibilities.